The cochlea of the Sima de los Huesos hominins (Sierra de Atapuerca, Spain): New insights into cochlear evolution in the genus Homo. Issue 136 (November 2019) - Conde-Valverde, Mercedes; Martínez, Ignacio; Quam, Rolf M.; Bonmatí, Alejandro; Lorenzo, Carlos; Velez, Alex D.; Martínez-Calvo, Carolina; Arsuaga, Juan Luis
Abstract: The cochlea contains taxonomic and phylogenetic information and its morphology is related with hearing abilities among fossil hominins. Data for the genus Homo is presently limited to early Homo and the early Neandertals from Krapina. The present study of the middle Pleistocene hominins from the Sima de los Huesos (SH) provides new evidence on cochlear evolution in the genus Homo . We compared the absolute length, proportional lengths of each turn, number of turns, size and shape of the cross-section of the basal turn, volume, curvature gradient, and thickness of the cochlea between extant Pan troglodytes, extant Homo sapiens, Homo neanderthalensis and the SH hominins. The SH hominins resemble P. troglodytes in the proportionally long basal turn, the small size and round shape of the cross-section of the basal turn, the small cochlear volume and the low cochlear thickness. The SH hominins resemble Neandertals and H. sapiens in their long cochlear length and in the proportionally short third turn. Homo neanderthalensis and H. sapiens share several features, not present in the SH hominins, and that likely represent homoplasies: a larger volume, larger size and oval shape of the cross-section of the basal turn and higher cochlear thickness. Later Neandertals show a derived proportionally shorter apical turn. Changes in cochlear volume in Homo cannot be fully explained by variation in body mass or cochlear length but are more directly related to changes in the cross-sectional area of the basal turn. Based on previous studies of the outer and middle ear in SH hominins, changes in the outer and middle ear preceded changes in the inner ear, and the cochlea and semicircular canals seem to have evolved independently in the Neandertal clade. Finally, the small cochlear volume in the SH hominins suggests a slightly higher upper limit of hearing compared with modern humans.